Policy Reforms and Agriculture Development in Central Asia - Djalalov, Sandjar; Babu, Suresh Chandra; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2006)
The Central Asian republics – Kazakhstan, the Krygyz Republic, Tajikistan, Turkmenistan, and Uzbekistan – are transitioning from centrally planned economies to market-oriented systems. This volume addresses the process and policy reforms these countries face and how the reforms may impact agricultural development in a region that has experienced varying degrees of economic growth over the fifteen years since independence. It offers expert policy research and analysis and provides research-based information for generating policy recommendations that are relevant to each country as well as similar evidence from other transitional economies, including China, Vietnam, and selected Eastern European countries. Suresh Chandra Babu is a Senior Research Fellow and Program Leader at the International Food Research Policy Institute (IFRPI), in Washington, D.C. where he coordinates its research and outreach programs in Central Asia. He has trained more than 1,000 policy analysts and has consulted with international organizations such as the World Bank, the Asian Development Bank, and UNICEF. Dr. Babu received his Ph.D. in economics from Iowa State University in the United States. Sandjar Djalalov is a principal researcher at the Center for Efficient Economic Policy in Uzbekistan where he conducts research on production, marketing, investment, and consumption behavior of different types of farms in Uzbekistan and Central Asia. He is also a senior lecturer in the Tashkent Institute of Engineering for Irrigation and Agricultural Mechanization. Dr. Djalalov received his Ph.D. from the Institute of Macroeconomics and Social Investigation in Tashkent in Uzbekistan.
Policy Reforms and Agriculture Development in Central Asia: An Overview of Issues and Challenges -- Economic Reform and Performance in Central Asia -- Agriculture Development in Central Asia: Trends and Analysis of Policy Reforms -- Political Economy of Agrarian Reforms in Central Asia: Lessons from Policy Failures -- Policy Reforms in Central Asia: Problems and Perspectives -- A Comparative Analysis of Trends in Agricultural Productivity in Central Asian Transition Economies -- Land Reform and Farm Restructuring in Central Asia: Progress and Challenges Ahead -- Globalization, Water and Changing Policies in the Aral Sea Basin -- Agriculture Reform Policies in Uzbekistan -- Policy Reforms and Agriculture Development Challenges in Tajikstan -- Agrarian Reforms in Turkmenistan -- Establishing the Sectoral Linkages in Policy Reforms -- Impact of Policy Reforms on Farm Production in Uzbekistan -- Farmers’ Response to Land Privatization in Tajikistan -- Market Reform and Producer Responses in Central Asia -- Policy Reforms and Livestock Development in Central Asia -- Private Sector Development in Uzbekistan Agriculture: Challenges and Opportunities -- Institutional Reforms and National Agricultural Research Systems in Central Asia -- Irrigation Systems and Sustainable Natural Resource Use Under Economic Reforms in Uzbekistan -- The Sustainable Development of Water User’s Associations in Uzbekistan -- Policy Reforms, Poverty and Food Security -- Food Security and Poverty in Central Asia -- Policy Reforms and Poverty in Central Asia with Special Focus on Kyrgystan -- Food Security and Determinants of Poverty in Central Asia: Case Study from Kazakhstan -- Future Challenges and Conclusions -- Information and Communication Technology in Reforming National Agricultural Systems in Central Asian Countries: The Case of Georgia -- Strengthening Institutional Capacity for Policy Reforms in Central Asia -- Policy Reforms in Central Asian Agriculture: A Synthesis and Conclusion.
Keywords: Agricultural economics; Development economics; Economic policy; Agricultural Economics; Development Economics; Economic Policy